Desain Penelitian Studi Kasus (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Case study research is one of the methodologies in qualitative research that seeks to investigate phenomena comprehensively in a real-world context. This paper provides a comprehensive discussion of case study research design, covering various aspects ranging from definitions and types to the steps involved in implementation. Various types of case studies are explained based on expert opinions, including intrinsic, instrumental, and collective case studies, along with classifications of explanatory, exploratory, descriptive, and others. Furthermore, the systematic phases involved in conducting case study research are detailed, including problem formulation, data collection and analysis, and reporting of results. Focus on the use of triangulation techniques and contextual approaches are essential to ensure the validity of findings. By gaining an in-depth understanding of this design, it is hoped that students and researchers will be able to design case studies appropriately and make significant scientific contributions.